2021
DOI: 10.1111/pbi.13579
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing dynamics and evolutionary divergence during embryogenesis in wheat species

Abstract: Among polyploid species with complex genomic architecture, variations in the regulation of alternative splicing (AS) provide opportunities for transcriptional and proteomic plasticity and the potential for generating trait diversities. However, the evolution of AS and its influence on grain development in diploid grass and valuable polyploid wheat crops are poorly understood. To address this knowledge gap, we developed a pipeline for the analysis of alternatively spliced transcript isoforms, which takes the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 61 publications
3
21
0
Order By: Relevance
“…AS response to HE. AS was observed to respond to changes of external conditions (such as abiotic/biotic stresses) and internal genomic environment (including WGD and structure variations) in plants ( Staiger and Brown, 2013, Laloum et al, 2018, Gao et al, 2021, which contribute to diversity and complexity of functional genome through enlarging the variety of RNA isoforms (Graveley, 2001, Syed et al, 2012. HE-induced AS response provides an extra dimension to further understand the genetic consequences of allopolyploidy.…”
Section: He-inducedmentioning
confidence: 99%
See 1 more Smart Citation
“…AS response to HE. AS was observed to respond to changes of external conditions (such as abiotic/biotic stresses) and internal genomic environment (including WGD and structure variations) in plants ( Staiger and Brown, 2013, Laloum et al, 2018, Gao et al, 2021, which contribute to diversity and complexity of functional genome through enlarging the variety of RNA isoforms (Graveley, 2001, Syed et al, 2012. HE-induced AS response provides an extra dimension to further understand the genetic consequences of allopolyploidy.…”
Section: He-inducedmentioning
confidence: 99%
“…This also raises new questions: besides junction regions, does HE also impact the expression of genes located within HE and on non-HE genomic regions? Moreover, recent studies showed that polyploidization and domestication can generate qualitative (gain and/or loss) changes of AS events in natural wheat species (Yu et al, 2020, Gao et al, 2021. So, is the direct effect of HE on AS in synthetic allopolyploids similar to that seen in established allopolyploid species that experienced natural selection and domestication?…”
Section: Introductionmentioning
confidence: 99%
“…Alternative splicing (AS) is a key post-transcriptional regulatory mechanism for expanding proteomic diversity and functional complexity [ 12 ], even generating trait diversity [ 13 ]. AS mainly results in generation of an alternative 3′ or 5′ splicing site (Alt 3′ ss and Alt 5′ ss, respectively),) intron retention (IR), and exon skipping (ES) [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alternative splicing (AS) is a key post-transcriptional regulatory mechanism for expanding proteomic diversity and functional complexity [ 12 ], even generating trait diversity [ 13 ]. AS mainly results in generation of an alternative 3′ or 5′ splicing site (Alt 3′ ss and Alt 5′ ss, respectively),) intron retention (IR), and exon skipping (ES) [ 13 , 14 ]. AS can produce truncated proteins, disrupting key domains or abolishing interaction with other proteins and thereby preventing the formation of functional protein complexes [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, whether alternative splicing is conserved has conflicting evidence with suggestions of both rapid divergence (Roy and Irimia 2009;Barbosa-Morais, et al 2012;Merkin, et al 2012) and conservation in splicing regulation. Specifically, sex determination genes in insects with sex specific splicing (Burtis and Baker 1989;Telonis-Scott, et al 2009;Salz and Erickson 2010;Graveley, et al 2011;Rogers, et al 2021) and developmental stage specific splicing Gao, et al 2021;Mazin, et al 2021).…”
Section: Introductionmentioning
confidence: 99%